2013
DOI: 10.1016/j.febslet.2013.09.032
|View full text |Cite
|
Sign up to set email alerts
|

NMR localization of the O‐mycoloylation on PorH, a channel forming peptide from Corynebacterium glutamicum

Abstract: a b s t r a c tPorH and PorA are two small peptides that, in complex, form a voltage-dependent ion channel in the outer membrane of Corynebacterium glutamicum. Specific post-translational modifications on PorA and PorH are required for the formation of a functional ion channel. The assignment of PorH proton NMR chemical shifts in DMSO, allowed identifying unambiguously the exact position of the PorH Omycoloylation on Ser 56 side chain. This was further confirmed by site directed mutagenesis and mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…diphtheriae [ 6 ]. This post-translational modification occurs on serine residues [ 6 , 7 ] and hence represents the first example of protein O -acylation in prokaryotes. It is also the first occurrence of protein modification by mycolic acids (“mycoloylation”).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…diphtheriae [ 6 ]. This post-translational modification occurs on serine residues [ 6 , 7 ] and hence represents the first example of protein O -acylation in prokaryotes. It is also the first occurrence of protein modification by mycolic acids (“mycoloylation”).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their small size and putative oligomeric state, Corynebacterium porins also differentiate themselves from Gram-negative bacteria porins by a Mycolata-specific post-translational modification. Indeed, PorH and PorA, together with another small protein of unknown identity and function (ProtX) are modified by the covalent attachment of mycolic acids to serine residues [ 6 , 7 , 28 ]. The site of modification of PorA and PorH were determined as S15 and Ser56, respectively [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To decipher the putative role of O-mycoloylation in the biogenesis of mycomembrane-associated proteins, we used a strategy based on homologous expression and structural characterization of the four major porins in C. glutamicum, all of which are found or thought to be found in the mycomembrane. This set includes the cation-selective channels PorA and PorH, which do not contain any leader sequence and are posttranslationally modified by a mycolic acid on serine residues S15 and S56 (6,9), respectively. In addition, we selected the anion-selective channel PorB and its homolog PorC containing 99 and 97 residues, respectively, after proteolytic cleavage of the N-terminal signal sequence specific for the Sec apparatus.…”
mentioning
confidence: 99%
“…: total six proteins including NCgl0329, NCgl0776, NCgl0933, NCgl2375, NCgl2430, and NCgl2779, were excluded because it was predicted by SignalP program that those proteins do not have signal peptide. Next, it is recently reported that O ‐mycoloylation of protein is a key post‐translational modification for localization of protein on mycolic acid layer . Proteins are transported and acylated with one or several mycolic acids by the cMytC on Ser residues located within short linear motifs (SS or SG), and through mycoloylation, protein has enhanced hydrophobicity which is the main driving force for mycomembrane localization.…”
Section: Resultsmentioning
confidence: 99%